THE URGENCY OF K.H. AHMAD DAHLAN'S THOUGHT AND ITS RELEVANCE TO MODERN EDUCATION - Khalim, Ahmad Dwi (Sunan Kalijaga International Journal on Islamic Educational Research, 2022)
The thought of K.H Ahmad Dahlan bears witness to history in this modern journey. The purpose of this study is to provide knowledge about the importance of K.H Ahmad Dahlan's thoughts on modern education. The approach used is a qualitative approach. The data sources in this study used primary sources from the work of Abdul Mu'thi, et al entitled K.H Ahmad Dahlan (1868-1923), and were supported by other sequence sources. In collecting this research data, it uses a descriptive method, namely a literature review. The first stepis to collect data, select data, describe and compile data according to the formulation of the problem, review the data and conclude. Test the validity of the data using triangulation, namely comparing or checking back with something different by checking between library data sources. K.H. Ahmad Dahlan's thoughts on education are four things including; 1.) educational objectives, 2.) educational materials, 3.) Learning methods. 4.) Learning models. The urgency of K.H. Ahmad Dahlan's thoughts on modern education can be seen from 1.) Law No. 20 of 2003, 2.) Permendikbud No. 21 of 2016 concerning Content Standards for Primary and Secondary Education, 3.) Permendikbud No. 22 of 2016 concerning Standards for Primary and Secondary Education Process, 4.) Permendikbud No. 67, 68, 69 and 70, Year 2013 concerning the Basic Framework and Curriculum Structure